An Integrated Pythagorean Fuzzy AHP & TOPSIS Method for the Selection of the Most Appropriate Clean Energy Technology - Karaşan, Ali; Kahraman, Cengiz; GÜNDOĞDU, FATMA KUTLU (My University, 2019)
Clean energy technologies which include renewable energy, electric vehicles, nuclear power and biofuels focus on ways to boost demand and de ployment by societies. Governments in many countries aim to increase the clean energy technologies and oner incentives to increase tendency on that sec tor. One of the reasons of these incentives is to prevent the global warming. For example. 30% of global electricity can be produced from wind and solar power in the long tenn, without adding to the total cost of reaching a low-carbon fu ture. In this study, we use an integrated Pythagorean fuzzy MCDM method consist of AHP and TOPSIS for the selection of the most appropriate clean en ergy7 technology for the Marmara Region.
Keywords: Pythagorean Fuzzy Sets; Pythagorean AHP; Pythagorean TOPSIS; Clean Energy7 Technologies; Decision Making Introduction